Knowledge Assessment And Application Psychological Skills Training (PST) In the Co-Curricular Trainer of the Malaysian Teacher Education Institute - Junaidy Mohamad Hashim; Mohad Anizu Mohd Noor (Pusat Kajian Pendidikan Olahraga Kesehatan Rekreasi, 2020)
The purpose of this study is to examine the level of knowledge and skills to apply the Psychological Skills Training (PST) among the Co-Curriculum Coaches of Malaysian Teachers' Teachers Institute which are randomly selected. A total of 77coches participated in this study consisting of 63 male coaches and 14 female coaches. The instrument for this study is a set of The Sports Psychology Revised Coach-2 (SPARC) questionnaire modified by the researchers based on the suitability. The questionnaire consists of 2 parts namely coaches demography and knowledge level Psychological Skills Training (PST) consisting of 10 items of questions and skilled to apply psychological Skills Training (PST) exercise sports psychology skills (10 items) based on Likert scale five values. An analysis is carried out descriptively involving frequency and percentage. The results based on application training showed that the method of self-talk training was very frequent and always applied, by 10 samples or 12.9%, followed by stress management training method by 6 samples or 7.8% and findings also showed that 66.2% or 51 samples did not apply the biofeedback training session method while training their athletes. Findings also showed that Co-Curriculum Coaches at the Malaysian Teachers Institute of Malaysia are less knowledgeable and less skilled to apply Psychological Skills Training (PST) even though the coaches have the qualifications in sports specific and sports science certificate at the highest level. 8% and findings also showed that 66.2% or 51 samples did not apply the biofeedback training session method while training their athletes. Findings also showed that Co-Curriculum Coaches at the Malaysian Teachers Institute of Malaysia are less knowledgeable and less skilled to apply Psychological Skills Training (PST) even though the coaches have the qualifications in sports specific and sports science certificate at the highest level. 8% and findings also showed that 66.2% or 51 samples did not apply the biofeedback training session method while training their athletes. Findings also showed that Co-Curriculum Coaches at the Malaysian Teachers Institute of Malaysia are less knowledgeable and less skilled to apply Psychological Skills Training (PST) even though the coaches have the qualifications in sports specific and sports science certificate at the highest level.